International sports managment: differences in approaches - Buriak, K. V.; Poliakova, O. O. (Національний технічний університет "Харківський політехнічний інститут", 2025)
Sports administration is shaped by cultural, economic, political, and social factors in various regions, making international sports management a complex field. This study examines the differences between major sports management models, focusing on the European, American, Asian, and Middle Eastern approaches. The research highlights the impact of globalization, digital technologies, and commercialization on sports management.
Keywords: sports administration; international sports managment; traditional approaches; mixed model; modern trends; globalization; digital technologies; commercialization